Medical technics - Ihde, Don, 1934- (Forerunners (Minneapolis, Minn.), 2019)
A personal account of the aging body and advanced technologies by a preeminent philosopher of technology. Medical Technics is a rigorous examination of how medical progress has modified our worlds and contributed to a virtual revolution in longevity. Don Ihde offers a unique autobiographical tour of medical events experienced in a decade, beginning in his 70s. Ihde offers experiential and postphenomenological analyses of technologies such as sonography and microsurgery, and ultimately asks what it means to increasingly become a cyborg.